PERAN PEMERINTAH DAERAH DALAM PENYELESAIAN KONFLIK AGRARIA : PENDEKATAN YURIDIS EMPIRIS DI PINRANG - Rahmi Rahmi; Zainal Said; Rezky Hidayah; Islamiyah Islamiyah; Ibnu Munzir; Andri Saputra (Universitas Ichsan Sidenreng Rappang, 2026)
This study aims to analyze the role of local government in resolving agrarian conflicts through an empirical juridical approach in Maccorawalie Village, Pinrang Regency. Agrarian conflict is a complex and multidimensional issue influenced by unequal land ownership, overlapping regulations, weak legal protection, and conflicts of interest between communities, the government, and private sectors. This research employed an empirical juridical legal research method with a qualitative descriptive approach. Data were collected through interviews, observations, and documentation using both primary and secondary data sources relevant to the research problem. The findings reveal that the role of local government in resolving agrarian conflicts has not been carried out optimally. The local government, which should function as a mediator, facilitator, regulator, and coordinator, has not been able to perform these roles effectively. This is reflected in the absence of mediation efforts, weak facilitation for the community, lack of policy intervention, and poor coordination among institutions. In addition, the effectiveness of the local government’s role is influenced by legal uncertainty, limited authority, weak institutional coordination, lack of active government involvement, and allegations of land mafia practices. The implementation of agrarian conflict resolution also demonstrates a gap between normative law (das sollen) and the realities in practice (das sein). This research is expected to contribute to the development of agrarian law studies and serve as an evaluation material for the government in creating a more effective, fair, and sustainable agrarian conflict resolution system.